Student-athletes on Twitter: a content analysis of media, gender and sentiment - Savatovic-Hathorn, Sara (Kansas State University, 2021)
Social networking sites (SNS) have become the primary communication tool of the 21st century. Every age and demographic is using SNS for different purposes (Pew Research Center, 2019). Not only general society got to make use of it, but also corporations took advantage of it and used it as a part of their marketing, branding, and customer relationship strategies (Leonardi et al., 2013). Indeed, sport teams and organizations are also benefiting from it (Pegoraro, 2010). Moreover, individuals who are heavily involved in online conversations are athletes (Sanderson & Kassing, 2011). The term athletes is very broad, therefore, this study was only focused on student-athletes. There are over 170,000 student-athletes competing in Division I (D1) National Collegiate Athletic Association (NCAA), the largest and richest out of all the divisions (NCAA, n.d.). To have a more exclusive sample, instead of focusing on the whole NCAA student-athlete population, this thesis only included the sport of basketball. Basketball is a high-revenue sport that fits both men and women, while the Big 12 Conference is one of the strongest conferences in the NCAAs (Ordway, 2020). The decision on the conference selection was due to the author of this study being a former Big 12 Conference student-athlete. Altogether, this study focused on Big12 Conference basketball student-athletes and aimed to understand how these student-athletes use social networking sites, specifically Twitter. This study used Meltwater, a software platform for media analytics, to determine key metrics, gender disparities and sentiment. Results demonstrate significant differences between males and females, and this thesis went further in describing those findings. Lastly, the findings of this study can be expected to add significant findings to how student-athletes use social media, which can inform future studies and athletic departments on social media use among other athletes.
Keywords: Social media; Twitter; Media analysis; Student-athletes; Gender disparities